2017
DOI: 10.1590/0034-7167-2017-0133
|View full text |Cite
|
Sign up to set email alerts
|

Association between filial responsibility when caring for parents and the caregivers overload

Abstract: Objective: To analyze the association between filial responsibility and the overload of the children when caring for their older parents. Method: Cross-sectional study with 100 caregiver children of older adults. Filial liability was assessed by the attitudes of the responsible child (scale of expectation and filial duty) and by care behaviors (assistance in activities of daily living, emotional and financial support, and keeping company). The overload was assessed by the Caregiver Burden Inventory. To assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 34 publications
(71 reference statements)
5
15
0
1
Order By: Relevance
“…(6) With regard to the characteristics of care, the more daily hours are spent on the care activities for the elderly bedridden, the greater the caregiver's perceived burden. This finding supports other studies in different contexts in Brazil (27,28) and internationally. (19) In Canada, the evaluation of the caregiver burden of stroke survivors revealed that the burden of caring for a dependent person is greater for the perceived time spent than for difficulties in carrying out care activities for the relative.…”
Section: Discussionsupporting
confidence: 92%
“…(6) With regard to the characteristics of care, the more daily hours are spent on the care activities for the elderly bedridden, the greater the caregiver's perceived burden. This finding supports other studies in different contexts in Brazil (27,28) and internationally. (19) In Canada, the evaluation of the caregiver burden of stroke survivors revealed that the burden of caring for a dependent person is greater for the perceived time spent than for difficulties in carrying out care activities for the relative.…”
Section: Discussionsupporting
confidence: 92%
“…This is different from studies from other parts of the world, where adult children may do whatever necessary including providing financial support (Abalos, Yasuhiko Saito, Cruz, & G.T. & Booth, H., 2018; Aires et al, 2017; Mendez‐Luck, Kennedy, & Wallace, 2008). However, this mutual agreement is consistent with findings of prior studies by Haberkern and Szydlik (2010) and Suanet, Groenou, and Tilburg (2012), showing that most of the population in Western European countries favours government responsibility in this respect, especially in the Netherlands and the Scandinavian countries.…”
Section: Comprehensive Understanding and Discussionmentioning
confidence: 84%
“…This finding ratifies the results of a national study, in which it was identified that providing financial support was a factor related to the higher overload of caregiving children. (16) In addition, as identified in another study, (27) financial issues in the process of caring for dependent parents are children's concerns. It is also added that many children are responsible for meeting the financial demands of the elderly parents, which consequently entails a financial burden on the caregiver.…”
Section: Discussionmentioning
confidence: 97%
“…(7) In Brazil, studies with elderly caregivers in general focus on the characterization of caregivers, their overload or quality of life and the needs to perform the care of the dependent elderly. (8)(9)(10)(11)(12)(13)(14)(15) Filial responsibility was the focus of a Brazilian research, (16) which analyzed the association between filial responsibility and overload of caregiving children, identifying formal employment (p = 0.027), having positive feelings in family life (p <0.001), providing financial support (p = 0.027) and helping in daily life activities (p < 0.001) as factors statistically associated with overload.…”
Section: Introductionmentioning
confidence: 99%